Relationships between slow vital capacity and measures of respiratory function on the ALSFRS-R. Issue 7 (2nd October 2018) - Jackson, Carlayne; De Carvalho, Mamede; Genge, Angela; Heiman-Patterson, Terry; Shefner, Jeremy M.; Wei, Jenny; Wolff, Andrew A.
Abstract: Objective : As declining respiratory muscle function commonly leads to disability and death in amyotrophic lateral sclerosis (ALS), respiratory measurements such as slow vital capacity (SVC) may predict disease progression. This study evaluated the relationship between SVC and symptoms measured by the revised ALS Functional Rating Scale (ALSFRS-R). Methods : About 453 ALS placebo-treated patients from the EMPOWER trial (NCT01281189) were evaluated. Correlations between %predicted SVC and individual respiratory ALSFRS-R subdomain items, respiratory subdomain score (maximum score of 12), and total ALSFRS-R score (maximum score of 48) were evaluated using the Pearson correlation coefficient. Pearson's chi-squared test was used to evaluate changes from baseline to week 48 in ALSFRS-R respiratory symptom and respiratory subdomain scores in patients with baseline %predicted SVC above/below the median at baseline and with more slowly/more rapidly decreasing %predicted SVC. Results: The %predicted SVC showed significant correlations with dyspnea, orthopnoea, respiratory insufficiency, respiratory subdomain score, and total ALSFRS-R score (all p < 0.0001). Patients with baseline SVC values < median were significantly more likely than those with baseline SVC ≥ median to have a change in total ALSFRS-R respiratory subdomain score from 12 to <12 (40.9% vs. 30.2%, p = 0.0358) and from ≥10 to <10 (41.6% vs. 24.4%, p = 0.0005). Additionally, patients with smaller declines in SVC over time were significantly more likely to have smaller decreases in their respiratory subdomain scores ( p < 0.0001). Conclusions : The higher correlation between %predicted SVC and specific ALSFRS-R symptom scores in patients with rapidly versus more slowly progressing disease reinforces the importance of continually monitoring respiratory function throughout the disease course.